Organic electrochemistry: Synthesis and functionalization of β-lactams in the twenty-first century - Bortolami Martina (De Gruyter, 2021)
Organic electrochemistry is a technique that allows for the heterogeneous redox reactions avoiding both the use of stoichiometric amounts of redox reagents and the resulting formation of stoichiometric by-products. In fact, the redox reagent in these reactions is the electron, which is naturally eco-friendly and produces no side compounds. It is therefore quite obvious that electrochemistry can be classified as a “green” technology. The use of this methodology in the synthesis of β-lactams is not a novelty, but the growing interest in this class of biologically active compounds, due to the discovery of new fields of application (after a moment of decrease in interest due to antibiotic resistance) has been a stimulus for the search for more efficient electrochemical ways to synthesize and transform β-lactams. Thus, this review deals with the twenty-first-century applications of electroorganic technique to the chemistry of β-lactams, by analyzing first the syntheses classified by the type of reactions (cyclization, cycloaddition, etc.) and then by manipulating the β-lactam structure, using it as a synthon. Lastly, the importance of this technique is demonstrated by a study of a pilot plant scale reduction of a cephalosporanic acid derivative to a commercially important antibiotic.